Conserved asymmetry underpins homodimerization of Dicer-associated double-stranded RNA-binding proteins. Issue 21 (17th October 2017) - Heyam, Alex; Coupland, Claire E.; Dégut, Clément; Haley, Ruth A.; Baxter, Nicola J.; Jakob, Leonhard; Aguiar, Pedro M.; Meister, Gunter; Williamson, Michael P.; Lagos, Dimitris; Plevin, Michael J.
Abstract: Double-stranded RNA-binding domains (dsRBDs) are commonly found in modular proteins that interact with RNA. Two varieties of dsRBD exist: canonical Type A dsRBDs interact with dsRNA, while non-canonical Type B dsRBDs lack RNA-binding residues and instead interact with other proteins. In higher eukaryotes, the microRNA biogenesis enzyme Dicer forms a 1:1 association with a dsRNA-binding protein (dsRBP). Human Dicer associates with HIV TAR RNA-binding protein (TRBP) or protein activator of PKR (PACT), while Drosophila Dicer-1 associates with Loquacious (Loqs). In each case, the interaction involves a region of the protein that contains a Type B dsRBD. All three dsRBPs are reported to homodimerize, with the Dicer-binding region implicated in self-association. We report that these dsRBD homodimers display structural asymmetry and that this unusual self-association mechanism is conserved from flies to humans. We show that the core dsRBD is sufficient for homodimerization and that mutation of a conserved leucine residue abolishes self-association. We attribute differences in the self-association properties of Loqs, TRBP and PACT to divergence of the composition of the homodimerization interface. Modifications that make TRBP more like PACT enhance self-association. These data are examined in the context of miRNA biogenesis and the protein/protein interaction properties of Type B dsRBDs.